Hubungan antara Kepercayaan Diri dengan Kecemasan Bertanding pada Atlet Voli - Wijaya, Yuniko Andre; Purnomo, Jusuf Tjahjo (Universitas Muhammadiyah Metro, 2023)
Competitive anxiety is an unpleasant emotional reaction brought on by worry or fear that occurs when fear is triggered during competition. The athlete's self-confidence is one of the aspects that affects nervousness when competing. The purpose of this study is to ascertain the association between volleyball athletes levels of self-confidence and competition anxiety in Salatiga city. Quantitative research methods with a correlational design are employed. Purposive sampling was used in this study, which included a total of 90 participants. The Sport Anxiety Scale-2 (SAS) (α = 0.900) and the Self-confidence Scale (α= 0.967) were the instruments employed in this study. The analysis of the data revealed a significant inverse association between competition anxiety and selfconfidence in volleyball athletes in Salatiga city, with rs = -0.498 and α = 0.000 (< 0.01).Athletes will have low competition anxiety if they have high self-confidence, so that when athletes are able to have confidence in their abilities, it will minimize anxiety in competing.